Film censorship in Egypt: power and subject-making - El Adl, Sara (AUC Knowledge Fountain, 2014)
This study’s focus is censorship on film in Egypt from 1971 onwards; when the first sign of incorporating religion as a source of law appeared with the addition of article 2, which states that “Islamic Shari’a is a main source of legislation.” Film is the most culturally powerful artistic medium in the Egyptian society due its mass consumption and has, from its point of introduction, served as a mirror into Egyptian politics and morality. Foucault’s mission of understanding how “subjectivity” forms and the power relations/modes that bring it about is a lens through which this project intends to examine the dynamic of artists, artistic material and their relationship to different power mechanisms in Egypt as they induce subjectivity. This study argues that the Egyptian state operates within a certain power dynamic that has allowed the freezing of a moral framework, which began in the 1970s. This framework began with a constitutional makeup that intended to and was successful in making a specific moral and religious ideal permanent, allowing it to permeate Egyptian society, and which can be traced through observing censorship of film. This dynamic has resulted in a peculiar reaction from artists and intellectuals, along with the public, who, holding on to a moral archetype that needs to be protected by the state, have accepted the concept of censorship to varying degrees, and have all at one point deemed it somehow necessary rather than revolted against it.